Early Restoration Of Upper Limb Function In Patients With Clavicle Fractures (Eurasian Medical Research Periodical, 2024)
Clavicle fractures account for 10 to 19.5% of all musculoskeletal fractures and adverse outcome rates range from 12.5 to 33.3%. Despite the variety of treatment . methods developed, in most cases they are not effective enough and it takes a long time to restore the function of the upper extremity.